Applying the life cycle assessment method to an analysis of the environmental impact of heat generation - Dzikuć, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a method of Life Cycle Assessment (LCA) to determine the impact of the heat produced on the environment. In addition, the usefulness of this method to assess the energy sector has been shown. This paper presents the impact of heat generation on the environment in coal power plants. A detailed analysis by the method of LCA is made to compare the environmental impact of heat generation in the Legnica Power Plant and Polkowice Power Plant. It is pointed to the difference in the results obtained. Moreover, the causes of the reported environmental impacts are discussed. Measures are identified which will help to reduce in the future the impact of the electricity produced on the environment during the production of heat.
Keywords: Life Cycle Assessment; energy; ecology; heat; power plants